Escola ciclada em Mato Grosso : desafios e possibilidades para o enfrentamento do fracasso escolar (Rondonópolis/MT 1998 - 2011) - Bezerra, Sílvia Maria Cavalcante Silva (2013)
This work is in the reflection and discussion of the challenges and possibilities for confronting school failure in Mato Grosso, proposed as an initiative by the state government through the State Department of Education in an attempt to mitigate the high levels of school failure with the implementation of the Basic Cycle Learning - CBA. The study aimed to understand the trajectory of the implementation of the Basic Cycle of Learning (CBA) in the state system of education, specifically in Rondonopolis-MT. I tried to understand three issues: a) the changes that happened in the educational practices of literacy, through the narratives of the subjects, depending on the deployment of cycling school in Mato Grosso, and b) the advances that brought cycling school for child literacy Rondonópolis / Mato Grosso and c) how the material offered with theoretical support influenced the design of literacy teachers. This is a production developed in the Master of Education Campus Rondonópolis / UFMT. The instruments adopted in the research were the testimonials and memorials, nine female subjects from five schools of the state in Rondonopolis / MT. I tried to analyze the impact of the CBA in the educational practices of literacy and assessment due to the implementation of the modality Literacy Basic Cycle. The analysis was based on historical background, in principle, the study's analysis of official documents that constitute the Proposed Curriculum for Basic Learning Cycle, consisting of nine books, published in 1998, and the proposal called cycling school of Mato Grosso: New times and spaces for teaching - learning to feel, and to be published in 2000. Among the procedures used include: a literature review and field, with document analysis and semi-structured questionnaires to various subjects of education, with a. purpose of knowing and collect data, anchored in memories and conceptions of the teachers interviewed, about the experience of the cycle in state schools in Rondonopolis / MT. Ancoro me in studies of authors such as: Mortatti, Patto, Ferraro & Machado, Freire, Marchesi and Perez Arroyo, Amancio, Resende, Maciel, Rovira, Lima, Freitas, Soares Barreto & Mitrulis, Cabrera, Araújo, Menegão, Araújo and Ribeiro, among others. The analysis could show that the speech of the teachers indicate positive and negative points about the implementation of the CBA, but also evidence that the discussions and studies in the Living Educator and training occurred during all these years has been important tools in addressing school failure.